Information control in the hold-up problem - Nguyen, Anh (2020)
We study the use of information control to mitigate hold-up risks. We identify a distinction between asymmetric information that creates an ex ante investment incentive and asymmetric information that causes ex post inefficiency, which then allows ex post inefficiency to be eliminated without compromising the ex ante investment incentive. We characterize the properties of the optimal information structure and the payoffs and welfare achievable with information control in the presence of hold-up risks.